2012
DOI: 10.1097/rct.0b013e3182680182
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography and Magnetic Resonance Imaging of Adult Renal Cell Carcinoma Associated With Xp11.2 Translocation

Abstract: The possibility of renal cell carcinoma associated with Xp11.2 translocation should be considered for a renal mass seen in a patient 45 years or younger, which demonstrates hemorrhage or necrosis or advanced stage disease at CT or MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
3
13
0
Order By: Relevance
“…The clinical pictures of Xp11.2 RCC described above were generally consistent with our findings. Additionally, CT and MR features of this rare disease had also been described [27][28][29], and we found that Xp11.2 RCCs showed large, well-defined and cystic-solid masses, often containing hemorrhage and circular calcifications on the CT, with hetero geneous, moderately prolonged enhancement after intravenous injection of contrast media [30].…”
Section: Resultsmentioning
confidence: 73%
“…The clinical pictures of Xp11.2 RCC described above were generally consistent with our findings. Additionally, CT and MR features of this rare disease had also been described [27][28][29], and we found that Xp11.2 RCCs showed large, well-defined and cystic-solid masses, often containing hemorrhage and circular calcifications on the CT, with hetero geneous, moderately prolonged enhancement after intravenous injection of contrast media [30].…”
Section: Resultsmentioning
confidence: 73%
“…However, due to the rarity of XP11.2 translocation RCC, only a few case reports focusing on its imaging features are available [11], [13][17]. MRI is suggested to be superior to CT due to the increased soft-tissue contrast and multiple imaging weights of MRI, which better reveal the heterogeneous composition (such as hemorrhage or necrosis) of this type of tumor [18].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other RCCs, its clinical process is more invasive with a poorer prognosis (10). Furthermore, the imaging manifestations of Xp11.2 translocation RCC are diverse, including hemorrhage, necrosis, cystic degeneration and calcification (8,(11)(12)(13)(14)(15). Therefore, the pre-operative diagnosis of this entity is occasionally difficult, as in the present case.…”
Section: Discussionmentioning
confidence: 69%